"Un film français et fier de l'être": Gaspar Noé's Climax in Context. Issue 1 (1st April 2021) - HAINGE, GREG
Abstract : Reading Gaspar Noé's 2018 film Climax against the grain of the majority of critical reactions and the director's own pronouncements, this article argues that this is a deeply political film. In line with West's analysis of the films of the New French Extremity as works that are not (as suggested by Quandt) passive but a committed and politically engaged form of cinema, this article suggests that Climax can be read as an allegory of France's current Realpolitik . Noé's vision of this reality is revealed to be particularly bleak, for in line with the metaphysical stance of his other films, his is a universe ruled by entropic forces. The ramifications for Climax 's commentary on contemporary France are devastating, for the ideals of the Republic are shown to be no longer operational or capable of bringing people together, nor are they replaceable by any other form of identity politics.